Desenvolvimento de um sensor óptico de salinidade baseados em fibras ópticas plásticas em formato U - Zanella, Fellipe Meneghim (2024)
Salinity is a physicochemical parameter measured and investigated in chemical, biological, food and oceanography areas. This work presents the development of a compact, easy-tomanufacture and low-cost salinity sensor using plastic optical fibers (POFs) laterally polished and bent in a U shape, with different curvature diameters and depths. The experiments were conducted with salt concentrations ranging from 0 to 25.9%, dissolved in water at room temperature of 20°C. The optical source used was a driver circuit for LED associated with a photodiode. An attenuation in the electrical voltage measured at the optical fiber output was observed due to the interaction of light with the salt concentrations used. Nine sensors were obtained, which presented linearities between R² 0.9822 and 0.9999, with sensitivities of -0.0196 V/% to -0.0712 V/% between the electrical voltage and the salt concentration. The best performing sensor showed a linearity of R² of 0.9999 and a sensitivity of -0.0712 V/% for a bend diameter of 7.65 mm, depth of 0.043 mm and length of 1.465 mm of the sensor detection region. In addition, a microcontrolled signal acquisition system was developed to measure the average sensor voltage, saline and ambient temperatures, along with relative humidity.